Pengaruh Kompetensi Sumber Daya Manusia, Pemahaman Akuntansi, Sistem Informasi Akuntansi, dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Koperasi di Kecamatan Buleleng - Hitawasana, Putu Jyestha; Dewi, Luh Gede Kusuma (Vokasi : Jurnal Riset Akuntansi, 2023)
This study aims to determine the effect of human resource competence, understanding of accounting, accounting information systems, and internal control systems on the quality of cooperative financial reports in Buleleng District. The population in this study are cooperatives located in the District of Buleleng. The data sampling used is purposive sampling method using certain criteria. The data are analysed by multiple linear regression analysis. The dependent variable in this study is the human resource competence, while the independent variables are the quality of financial reports, understanding of accounting, accounting information systems and internal control systems. The results of this study indicate that human resource competence, understanding of accounting, accounting information, and the internal control system has a significant positive effect on the quality of financial reports.